2018
DOI: 10.4314/as.v16i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pests control methods and its perceived effect on agricultural production among farmers in Kwara state, Nigeria

Abstract: The study examined the usage of chemical and biological pests control methods among the farmers in Kwara State, Nigeria. A three-stage random sampling technique was used to select 120 respondents. A well structure questionnaire was used to collect the data for the study. Descriptive statistics and partial correlation were used in analyzing the data. The study revealed that all the farmers were aware of the cultural pest control method, while 73.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…that cause economic losses in agricultural production. Insects and other species that damage crops and also infect humans or animals are therefore pests that should be controlled as much as possible [1]. Some of the harmful insects play a role as vector insect in the spread of important diseases such as virus diseases.…”
Section: Management Methods Of Insect Pestsmentioning
confidence: 99%
See 2 more Smart Citations
“…that cause economic losses in agricultural production. Insects and other species that damage crops and also infect humans or animals are therefore pests that should be controlled as much as possible [1]. Some of the harmful insects play a role as vector insect in the spread of important diseases such as virus diseases.…”
Section: Management Methods Of Insect Pestsmentioning
confidence: 99%
“…The word "pest" describes an organism that harms crops, harms or irritates animals or humans. Agricultural pests include insects, weeds, bacteria, viruses, fungi and animals that reduce crop yield relative to the potential yield that would be possible in a pest-free world [1]. Some of the epidemic diseases have been carried by insects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that 78.3% of the respondents attested to the efficacy of chemical pesticides in combatting the menace of armyworm is an indication of its extensive use among the maize farmers. Alalade et al [24] reported on the wideusage of chemical pesticides among farmers in Kwara state. The result was not unexpected because chemical use has been a common practice to combat pest infestations before the advent of Fall armyworm in the State.…”
Section: The Use Of Chemical Controlmentioning
confidence: 99%
“…Integrated Pest Management (IPM) is a sustainable approach that provides an alternative to the sole use of pesticides for pest management. IPM aims to promote sustainability in agriculture by employing pest management options that reduce crop losses and increase productivity without the negative environmental and health impacts associated with exclusive pesticide application (Van Huis and Meerman, 1997;Ojumoola et al, 2016;Alalade et al, 2017). Amongst other requirements, good understanding of the diversity and role of insects within cropping systems will be needed for a successful IPM programme (Nwilene et al, 2008).…”
Section: Introductionmentioning
confidence: 99%